Garbage Pail Kids - Pound, John; Spiegelman, Art (Abrams Comic Art, 2012)
A series of collectible stickers produced by Topps in the 1980s combined spectacular artwork and over-the-top satire. The result was an inspired collaboration between avant-garde cartoonists and humorists including Art Spiegelman, Mark Newgarden, John Pound, Tom Bunk, and Jay Lynch. A new generation of fans continues to embrace this pop-culture phenomenon as Garbage Pail Kids stickers are still being published. Now, for the first time, all 206 rare and hard-to-find images from Series 1 through 5 are collected in an innovative package, along with a special set of four limited-edition, previously unreleased bonus stickers. This exciting follow up to Wacky Packages is guaranteed to appeal to die-hard collectors as well as a new generation of fans.